Rancang Bangun Aplikasi Pencarian Bengkel Motor Berbasis Android Di Wilayah Kota Bekasi - Elmi Devia; Junaidi; Hendro Agus Sumantri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Motor vehicles are increasing in number, almost everyone has a personal motorbike. Every engine needs maintenance, including motorcycles. Manufacturers always recommend that maintenance be carried out at their respective ATPM (Sole Agent Brand) motorcycle repair shops, but it is possible that people will choose non-ATPM workshops if they are faced with the situation of choosing the nearest motorcycle repair shop. Along with the development of information, technology, especially in android-based mobile applications, research was carried out to create an android-based motorcycle repair search application so that it can assist the community in finding the location of the nearest motorcycle repair shop in Bekasi City, with GPS (Global Positioning System) and Google Maps services.